2021
DOI: 10.1080/1461670x.2021.1979426
|View full text |Cite
|
Sign up to set email alerts
|

How Does an Incumbent News Media Organization Become a Platform? Employing Intra-Firm Synergies to Launch the Platform Business Model in a News Agency

Abstract: Digital platforms have disrupted traditional news organizations, with new platform-based models gaining ground. However, the incumbents can defend their positions and reap the benefits of multisided market structures by establishing a platform business model themselves. We examine a case study of the Austrian News Agency (APA), which gradually formulated a strategy that resulted in a platform-based business model. Platform features were strategized and innovated over time and in phases, with the intent of crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…The business model transformations required at each step are different and revolve mainly around the structure of a platform market, as well as the production-(e.g., supply-) and demand-side choices regarding the platform governance and platform architecture (Jacobides et al, 2018). At each step, the platform and ecosystem logic can be unlocked to different degrees (Jääskeläinen et al, 2021). The trajectory and the key choices along the way are depicted in Figure 1.…”
Section: Evolutionary Model Of Platform Business Model Innovation In ...mentioning
confidence: 99%
“…The business model transformations required at each step are different and revolve mainly around the structure of a platform market, as well as the production-(e.g., supply-) and demand-side choices regarding the platform governance and platform architecture (Jacobides et al, 2018). At each step, the platform and ecosystem logic can be unlocked to different degrees (Jääskeläinen et al, 2021). The trajectory and the key choices along the way are depicted in Figure 1.…”
Section: Evolutionary Model Of Platform Business Model Innovation In ...mentioning
confidence: 99%
“…In parallel with the debate on disruptive innovation, another research stream, digital innovation, and entrepreneurship, has been rapidly developed due to the emergence of digital technologies. Various insights have been contributed, involving digital business models ( Klos et al, 2021 ), digital entrepreneurship process ( Lin and Maruping, 2022 ), platform strategies ( Jääskeläinen et al, 2021 ), and digital ecosystem ( Beltagui et al, 2020 ), etc. Among them, the disruptive implications of digital technologies for businesses have been greatly highlighted ( Nambisan et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The application of digital technology is extending the scope of business model deployment and accelerating business model innovation ( Lu and Yu, 2022 ). A series of novel business models embedded in the digital context have been developed, such as the platform business model ( Jääskeläinen et al, 2021 ), which reveal the novel characteristics of servitization, agility, and value co-creation. Moreover, the dynamic evolutionary feature of business model in the rapidly developing digital era appears more obvious ( Bohnsack et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although many papers propose transforming pipeline business models into digital platform business model, only a few studies investigate the antecedents and drivers of this process. These studies provide evidence that trusted institution legitimacy, cooperative organizational model, founders' experiences, entrepreneurial orientation, industry influences, as well as environmental characteristics are relevant antecedents to pipelines business models transform themselves in DPBM (Jääskeläinen et al, 2021;Rumble & Mangematin, 2015;Su et al, 2020). Furthermore, this stream has identified that servitization is a relevant driver for DPBM (Kohtamäki et al, 2019).…”
Section: Dpbm Antecedentesmentioning
confidence: 89%
“…The main purpose of these articles is to explain how these industries can have better outcomes by adopting digital platform' business models. We found 4 papers describing the transformation process from a pipeline business model to a digital platform' business model which contributes to identifying lessons learned in the process (Dell'Era, Trabucchi, & Magistretti, 2021;Gustavsson & Ljungberg, 2020;Jääskeläinen, Yanatma, and Yanatma, 2021;Wesselius, 2008). Another significant characteristic of this theme is that, although using different business model frameworks, 34.1% (n = 14) of the studies do not discuss any theory.…”
Section: Business Model Innovation To Dpbmmentioning
confidence: 99%